Oral Lycopene Administration Attenuates Inflammation and Oxidative Stress by Regulating Plasma Lipids in Rats with Lipopolysaccharide-Induced Epididymitis - Li Y; Zhu J; Zhao X; Sun Y; Xu F; Xu S; Shang X (Dove Medical Press, 2022)
Yu Li,1 Jinde Zhu,1 Xiaodong Zhao,2 Yi Sun,2,3 Feng Xu,1,2 Song Xu,1,2 Xuejun Shang1,2 1Department of Urology, Jinling Hospital, The First School of Clinical Medicine, Southern Medical University, Nanjing, People's Republic of China; 2Department of Urology, Jinling Clinical Medical College of Nanjing Medical University, Nanjing, People's Republic of China; 3Department of Pathology, Jiangsu Province Hospital of Chinese Medicine, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, People's Republic of ChinaCorrespondence: Xuejun Shang, Department of Urology, Jinling Hospital, The First School of Clinical Medicine, Southern Medical University, No. 305 East Zhongshan Road, Nanjing, 210002, People's Republic of China, Tel +8613813905418, Email shangxj98@163.comPurpose: Epididymitis histological alterations and related long-term reproductive issues cannot be cured by antibiotics alone. Few studies have been done on the effect of lycopene on epididymitis, despite the fact that it is an efficient antioxidant. The objective of this study was to assess the impact of lycopene on Lipopolysaccharide (LPS)-induced epididymis and lipid metabolism.Methods: Thirty-one 260- 290g rats were separated into the blank control group (n=10), the oil-control group (n=10), the single intraperitoneal injection of 5 mg/kg LPS (n=5), and the continuous intragastric of 5 mg/kg lycopene (n=6). The animals were euthanized after four weeks, and blood and the epididymis were removed for analysis.Results: Lycopene significantly decreased IL-1α, IL-1β, TNF-α, MCP-1, IL-6 and lipid peroxidation product Malondialdehyde in serum and epididymis. It significantly increased the epididymis's antioxidant enzyme and total antioxidant capacity. According to LC-MS plasma lipidomics, lycopene increased phosphatidylcholine, lysophosphatidylcholine, decreased phosphatidylethanolamine, triacylglycerol, and diacylglycerol levels, changed the composition of lipids, altered metabolic pathways, and these changes were related to the mechanism of anti-inflammatory and oxidative stress. 20 lipids, including PC (20:5e) and LPC (14:0), were identified through additional Spearman correlation analysis as being related to cytokines and oxidation indices. They served as possible lipid markers that may be utilized to gauge the severity of inflammation.Conclusion: Lycopene has anti-inflammatory and antioxidant properties that improve histopathological and functional damage in LPS-induced epididymitis and is an alternate supplement for treating epididymitis. Lipidomics provide new perspectives on the possible mechanism of lycopene in protecting against LPS-induced epididymitis by integrating lipid metabolism and inflammation.Keywords: lycopene, lipidomics, inflammatory, antioxidant, lipids regulation, correlation